2011
DOI: 10.1016/j.jtcvs.2010.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Transient mitochondrial permeability transition pore opening after neonatal cardioplegic arrest

Abstract: Apoptosis-related mitochondrial dysfunction in postcardioplegic neonatal hearts is mediated by mitochondrial permeability transition pore opening, which is transient and associated with deficits in electron transport. Clinical strategies directed to minimize mitochondrial permeability transition pore opening are likely to improve postoperative myocardial dysfunction after neonatal cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The majority of experimental studies investigating the cardioprotective effects of CsA have focused on reducing myocardial infarct size using an animal model of IRI, which most closely recapitulates the acute IRI experienced by the STEMI patient undergoing PPCI. However, CsA has also been reported to protect the heart against acute IRI in other experimental settings such as neonatal cardioplegic arrest and reperfusion (Oka et al ., 2008; Leung et al ., 2011) and resuscitated cardiac arrest (Cour et al ., 2011). By measuring the mitochondrial entrapment of titriated glucose at reperfusion following cardioplegic arrest, Leung and co‐workers (Leung et al ., 2011) demonstrated that in a neonatal rabbit model of cardioplegic arrest and reperfusion, CsA‐sensitive mPTP opening occurs at the time of myocardial reperfusion, providing preliminary experimental evidence that treatment with CsA or another mPTP inhibitor may be beneficial in terms of reducing perioperative myocardial injury in neonates undergoing corrective cardiac surgery for congenital heart disease.…”
Section: Protecting the Heart In Other Settings Using Csamentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of experimental studies investigating the cardioprotective effects of CsA have focused on reducing myocardial infarct size using an animal model of IRI, which most closely recapitulates the acute IRI experienced by the STEMI patient undergoing PPCI. However, CsA has also been reported to protect the heart against acute IRI in other experimental settings such as neonatal cardioplegic arrest and reperfusion (Oka et al ., 2008; Leung et al ., 2011) and resuscitated cardiac arrest (Cour et al ., 2011). By measuring the mitochondrial entrapment of titriated glucose at reperfusion following cardioplegic arrest, Leung and co‐workers (Leung et al ., 2011) demonstrated that in a neonatal rabbit model of cardioplegic arrest and reperfusion, CsA‐sensitive mPTP opening occurs at the time of myocardial reperfusion, providing preliminary experimental evidence that treatment with CsA or another mPTP inhibitor may be beneficial in terms of reducing perioperative myocardial injury in neonates undergoing corrective cardiac surgery for congenital heart disease.…”
Section: Protecting the Heart In Other Settings Using Csamentioning
confidence: 99%
“…However, CsA has also been reported to protect the heart against acute IRI in other experimental settings such as neonatal cardioplegic arrest and reperfusion (Oka et al ., 2008; Leung et al ., 2011) and resuscitated cardiac arrest (Cour et al ., 2011). By measuring the mitochondrial entrapment of titriated glucose at reperfusion following cardioplegic arrest, Leung and co‐workers (Leung et al ., 2011) demonstrated that in a neonatal rabbit model of cardioplegic arrest and reperfusion, CsA‐sensitive mPTP opening occurs at the time of myocardial reperfusion, providing preliminary experimental evidence that treatment with CsA or another mPTP inhibitor may be beneficial in terms of reducing perioperative myocardial injury in neonates undergoing corrective cardiac surgery for congenital heart disease. In another study, Cour and colleagues (Cour et al ., 2011) found that administering either intravenous CsA (5 mg·kg −1 ) or N‐methyl‐4‐isoleucine cyclosporin (NIM811) (2.5 mg·kg −1 ) at the time of reperfusion following a 15 min period of primary asphyxial in situ cardiac arrest in rabbits improved survival, reduced myocardial necrosis and inhibited mPTP opening in isolated cardiac mitochondria.…”
Section: Protecting the Heart In Other Settings Using Csamentioning
confidence: 99%
“…The PTP has long been a target for the protection of both myocytes and mitochondria during ischemia and reperfusion (27). Opening of the PTP results in mitochondrial calcium overload, release of reactive oxygen species, and apoptosis (28,29) in both adults and children. The use of pharmacology to prevent PTP opening has not significantly impacted clinical outcomes in adult cardiac ischemia (30).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in post-cardiac arrest myocardial dysfunction, apoptosis in the context of mPTP opening is much more common in the neonatal myocardium after cardioplegic arrest [94]. Inhibition of mPTP opening in neonatal cardioplegic arrest in rabbits with cyclosporine A improves myocardial function and CI respiration and reduces ROS production [94,95]. In a direct comparison of neonatal (6–8 days) and young adult (6–8 weeks) lambs who underwent cardioplegic arrest for cardiopulmonary bypass, neonatal myocardium exhibited more evidence of mPTP opening, characterized by increased cytochrome c release, caspase activity, and apoptosis [96].…”
Section: Role Of the Mitochondrial Permeability Transition Porementioning
confidence: 99%